Effect of supplemental carbohydrate type and amount of ruminally degradable protein on utilization of tallgrass-prairie hay by beef steers - Arroguy, J.I.; Cochran, R.C.; Villarreal, M.; Wickersham, T.A.; Llewellyn, Donald A.; Johnson, D.E.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This experiment determined the impact of type of supplemental carbohydrate and amount of supplemental ruminally degradable protein (RDP) on intake and digestion of prairie hay. Fourteen ruminally fistulated beef steers were supplemented with one of two carbohydrates (corn starch or the simple sugar glucose) at 0.30% of body weight and one of seven levels of ruminally degradable protein (RDP; 0, 0.015, 0.051, 0.087, 0.123, 0.159, or 0.195% of body weight). Two additional steers served as controls (non-supplemented steers, i.e., no carbohydrate or RDP supplementation). Forage intake and digestion were substantially improved by increasing amounts of supplemental RDP. Supplemental carbohydrate with insufficient supplemental RDP depressed fiber digestion although carbohydrate type did not alter the digestion response or forage intake. In conclusion, when supplementing cattle eating low-quality forage, it is important to ensure that the supplement contains adequate RDP. The impact of the supplement on forage use should not differ greatly between starch (e.g., cereal grains) and sugar (e.g., molasses) as the main carbohydrate source.
Keywords: Beef; Supplemental carbohydrate; Protein; Tallgrass-prairie; Steers